From skin to heart: The rare journey of pleomorphic dermal sarcoma metastasis - Maria Gabriela Matta, MD MSc; Dipesh Raniga, MD; Vinicius Carraro do Nascimento, MD; Gayle Therese Hill, BSc; Mohamed Nasser Essack, MD; Ian Agahari, MD (Radiology Case Reports)
Cardiac tumours can be classified as neoplastic or non-neoplastic, with secondary tumours being significantly more common than primary ones. Among secondary tumours, melanoma has the highest propensity for cardiac involvement. Pleomorphic dermal sarcoma (PDS) is a rare skin neoplasm, with an estimated metastatic risk of 10% to 20%. This report presents the case of a 52-year-old male who, after a history of PDS, developed cardiac metastasis 4 years postexcision. Despite clear surgical margins and adjuvant radiotherapy, he later exhibited metastatic disease affecting the lungs and heart. Advanced imaging revealed tumour invasion into the left atrium, leading to palliative chemotherapy and ultimately the patient's transition to palliative care 7 months after diagnosis. This case underscores the need for vigilance in monitoring potential metastasis in rare tumours like PDS.